Selective adsorption in ion exchange membranes: The effect of solution ion composition on ion partitioning - Ozkul, S.; Arbabzadeh, O.; Bisselink, R. J. M.; Kuipers, N. J. M.; Bruning, H.; Rijnaarts, H. H. M.; Dykstra, J. E. (Water Research, 2024)
Electrodialysis is a water desalination technology that enables selective separation of ions, making it a promising solution for sustainable water reuse. The selectivity of the process is mainly determined by the properties of ion exchange membranes that can vary depending on the composition of ions in water, such as water uptake and charge density. In this work, we studied selective adsorption of Na+ and K+ ions in various ion exchange membranes considering the effect of solution ion composition on membrane water volume fraction. For that purpose, we conducted membrane adsorption experiments using solutions with Na+ and K+ ions with different ion compositions including Li+, Ca2+ or Mg2+ ions at different concentrations (0.001 – 0.25 M). The experiments showed that with the total ion concentration and the amount of divalent ions in solution, the membrane water volume fraction decreases while the selective adsorption of the smaller (hydrated) K+ ions over the Na+ ions in the membrane increases. We developed a theoretical framework based on Boublik-Mansoori-Carnahan-Starling-Leland (BMCSL) theory to describe the effect of membrane water volume fraction on selective adsorption of the ions by including volumetric effects, such as size exclusion. The developed framework was used to describe ion partitioning results of the membrane adsorption experiments. In addition, the effect of solution ion composition on selective ion removal during electrodialysis operation was evaluated using experimental data and theoretical calculations. The results of this study show that considering volumetric effects can improve the ion partitioning description in ion exchange membranes for solutions with various ion compositions.